A method for annealing modification of starch in slurry form

CN122978320APending Publication Date: 2026-10-27况小龙
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610881934.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,该技术以“脱水干燥”为核心目的,冷却仅是干燥过程的附带结果,冷却速率不受控制

Benefits of technology

(1)战略价值:封堵了竞争对手通过“浆态路线”和“中间含水量物料路线”绕开核心粉末调质退火工艺的全部空间。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a method for annealing modification treatment of starch in a slurry form, and belongs to the technical field of starch modification. The starch-containing raw material is mixed with water to prepare slurry material with a water content of 40%-60%, and then annealing is performed in a constant humidity environment with a relative humidity of 90%-95% for 10-20 minutes in a temperature window of 50-65 DEG C, so that part of gelatinized amylose molecules are orderly rearranged along the surface of residual natural starch microcrystals to generate RS3 type resistant starch. Subsequently, spreading and rapid cooling integrated forming is adopted, the slurry is spread into a thin layer within 90 seconds and is simultaneously cooled and shaped to below 35 DEG C to lock the RS3 crystal lattice, and finally low-temperature drying is performed. The spreading mode includes but is not limited to scraper spreading, flow forming, extrusion forming and roller pressing forming. The application is a pure physical zero-addition process, is suitable for low-protein or gluten-free starch raw materials such as rice starch, corn starch and potato starch, and the resistant starch content of the obtained product is greater than or equal to 7%, the GI value is less than or equal to 65, and the RS3 melting temperature is greater than or equal to 120 DEG C. The application is mainly used for blocking the possibility that competitors bypass the powder tempering and annealing core process through a "slurry route".
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of starch modification technology, specifically relating to a method for annealing in the form of a slurry material, applicable to starch-containing raw materials with low protein or no gluten. Background Technology Current starch annealing processes generally employ a powder conditioning route: starch or grain powder is atomized and sprayed with water to adjust the moisture content to 20%-35%, forming a loose, moist flocculent or fine granular material, which is then annealed. The advantages of this route are a large specific surface area of ​​the material, uniform heat transfer, and low drying energy consumption after annealing. However, in industrial practice, another possible pretreatment route exists: directly mixing starch raw materials with water to form a high-moisture (40%-60%) slurry, followed by annealing. The slurry route differs fundamentally from the powder conditioning route in material morphology, heat transfer, and drying methods. If competitors claim, "We don't add water to condition wet powder; we add water and stir it into a slurry, so we're not infringing," existing technologies lack systematic coverage of the slurry annealing route. Furthermore, drum drying technology is known in the art for the production of pregelatinized starch, in which starch slurry is spread into a film on the surface of a heated drum and dried. However, this technology focuses on "dehydration and drying," with cooling being merely a byproduct of the drying process, and the cooling rate is uncontrolled. No prior art has ever taught or inspired the use of spreading as a rapid cooling method to simultaneously lock the RS3 lattice. This invention is the first to systematically study the slurry annealing process window and creatively couples spreading and rapid cooling into an integrated operation: the spreading action itself serves as a rapid cooling method, cooling the material from the annealing temperature to below 35°C within 90 seconds. This design breaks through the traditional two-step mode of "drying first and then cooling" and realizes a new process logic of "rapid cooling to lock the crystal lattice first, and then drying and dehydrating". Summary of the Invention Purpose of the invention The purpose of this invention is to provide a method for annealing starch in the form of a slurry. Through systematic process design in slurry preparation, annealing, spreading and rapid cooling integrated molding, spreading is used as a rapid cooling method to lock the RS3 lattice, so as to achieve product compliance. At the same time, it blocks all possibilities for competitors to circumvent the core powder conditioning and annealing process through the "slurry route" and "intermediate moisture content material route". Technical solution This invention adopts a novel technical approach of "slurry annealing + spreading and rapid cooling integrated molding", which includes the following steps: (1) Pulping: Mix low-protein or gluten-free starch-containing raw materials with water and stir to make a uniform, flowable slurry with a water content of 40%-60%. (2) Slurry annealing: In a constant humidity environment with a relative humidity of 90%-95%, maintain at 50-65℃ for 10-20 minutes. Due to the large heat capacity and high convective heat transfer efficiency of slurry materials, heat can quickly and evenly penetrate into the interior of the material. (3) Integrated Spreading and Rapid Cooling Molding: The annealed slurry is spread into a thin layer with a thickness not exceeding 3 mm within 90 seconds and simultaneously cooled to below 35°C. The spreading method includes, but is not limited to, scraper spreading, casting, extrusion molding, roll forming, and all other methods that convert the slurry into a thin layer and simultaneously cool it during the spreading process. This step uses spreading as a rapid cooling method—the specific surface area increases sharply the instant the slurry spreads to form a thin layer, and it simultaneously contacts the cold medium, thus completing rapid cooling. Drying is completed independently in subsequent steps. (4) Low temperature drying: Dry at no more than 60℃ to safe moisture content, then crush and sieve. The “pulping” described in step a is fundamentally different from the “water conditioning” in the applicant’s prior core patent: (1) Different material forms: This patent is a high-moisture-content flowable slurry material, while the core patent is a loose, damp, flocculent or granular material; (2) Different moisture content: This patent is 40%-60%, while the core patent is 20%-35%; (3) Different subsequent processing methods: This patent requires spreading and rapid cooling for integrated molding, while the core patent directly cools and dries. When the material's moisture content is in the intermediate range of 35%-40%, it is neither loose and flocculent nor a flowable slurry, but rather a paste or ointment. In this state, regardless of the molding method used, the lack of sufficient free water to form a continuous heat transfer medium leads to uneven heat transfer and insufficient starch hydration during annealing. Simultaneously, the material's poor flowability prevents uniform spreading or extrusion, and the annealing and rapid cooling effects cannot meet requirements (see Comparative Examples 1, 6, and 7). A moisture content of 40% is the absolute lower limit for the slurry-like path. Core Mechanism The high moisture content of slurry materials gives them a unique advantage in heat transfer during annealing. Unlike powder materials, which are heated primarily by conduction, the free water in slurry materials forms a continuous phase, allowing heat to be transferred rapidly and evenly to the surface of each starch granule through convection, while ensuring the full hydration and plasticization of the starch molecular chains. After annealing, this invention employs an "integrated spreading and rapid cooling molding" strategy: the slurry is spread into a thin layer, and the spreading action itself serves as a rapid cooling method. This thin-layer spreading dramatically increases the material's specific surface area, resulting in an exponentially increased cooling rate. Rapid cooling is completed within 90 seconds, "freezing" the RS3 lattice to its optimal state. This process logic is entirely different from the traditional drum drying logic of "primarily using heating for drying, supplemented by cooling." Regarding the risk of thermal damage: The water content of the slurry material is as high as 45%-55%. When it is spread on the surface of the drum heated at 75-85℃, the water evaporates and absorbs heat, resulting in a significant evaporative cooling effect. This causes the actual temperature of the material film to only reach 62-68℃ (measured data in Example 1), which is far lower than the melting temperature of RS3 (≥120℃). Therefore, it will not cause thermal damage to RS3. Beneficial effects (1) Strategic value: It blocks all the space for competitors to bypass the core powder conditioning and annealing process through the "slurry route" and the "intermediate moisture content material route". (2) Innovation in process logic: Breaking through the traditional two-step model of "drying first and then cooling", spreading is used as a rapid cooling method to achieve a new process logic of "rapid cooling to lock crystals first, and then drying and dehydration". (3) Flexible spreading method: Spreading and rapid cooling integrated molding can be achieved through various methods such as scraper spreading, casting molding, extrusion molding, and roll forming. (4) High heat transfer efficiency: slurry materials undergo convective heat transfer, resulting in good annealing uniformity. (5) Thermal safety is guaranteed: the evaporative cooling effect makes the actual temperature of the material much lower than the RS3 melting point. (6) Purely physical with zero additives: The ingredient list only contains the raw materials themselves. Detailed Implementation Example 1 (Rice flour slurry annealing, spread with a scraper) Take 1000g of rice flour (approximately 7% protein), add 1200mL of water, and stir to prepare a uniform, flowable slurry with a moisture content of approximately 55%. Place the slurry in a constant temperature and humidity container and anneal at 65℃ and 92% humidity for 15 minutes. After annealing, send the slurry to a scraper-type film dryer. This equipment includes a heating drum and a cooling drum arranged side by side. The scraper peels the film off the surface of the heating drum and directly introduces it onto the surface of the cooling drum, with a transfer time of no more than 5 seconds. The slurry spreads on the heating drum (surface temperature 80℃) to form a film with a thickness of approximately 1.5mm. Infrared thermometer measurements show that the surface temperature of the film is only 64-67℃ (due to the evaporative cooling effect). After initial dehydration to approximately 32% moisture content, the material is transferred to the cooling drum (surface temperature 5℃) for rapid cooling to below 30℃. The entire process, from the moment the slurry contacts the heating drum to the moment the film leaves the cooling drum, takes approximately 80 seconds. Scrape off thin sheets, dry at 50℃ until the moisture content is 12.0%, pulverize and pass through an 80-mesh sieve to obtain the product. Tests showed that the product contained 8.0% resistant starch, had a GI value of 62, and an RS3 melting temperature of 122℃. The product particles were scaly in shape. Example 2 (corn starch slurry annealing, scraper spreading) Take 1000g of corn starch, add 1000mL of water, and stir to make a uniform slurry with a moisture content of about 50%. Anneal at 62℃ and 90% humidity for 14 minutes. Spread and rapidly cool for integrated molding: heat the drum to 78℃, the actual temperature of the material film is about 60-63℃, the film thickness is about 2mm, and spread and cool to below 32℃ within 90 seconds. Dry at 48℃ to a moisture content of 12.5%, then pulverize and sieve. Test results show that the resistant starch content is 7.5%, the GI value is 64, and the RS3 melting temperature is 121℃. Example 3 (Antification of potato starch slurry, spread by scraper) Take 1000g of potato starch, add 1500mL of water, and stir to make a uniform slurry with a moisture content of about 60%. Anneal at 63℃ and 90% humidity for 12 minutes. Spread and rapidly cool for integrated molding: heat the drum to 82℃, the actual temperature of the material film is about 66-68℃, the film thickness is about 1mm, and spread and cool to below 28℃ are completed within 75 seconds. Dry at 50℃ to a moisture content of 12.8%, then pulverize and sieve. Test results show that the resistant starch content is 7.1%, the GI value is 65, and the RS3 melting temperature is 120℃. Example 4 (Rice flour slurry annealing, casting molding) Take 1000g of rice flour (approximately 7% protein), add 1200mL of water, and stir to form a uniform slurry with a moisture content of approximately 55%. Anneal at 65℃ and 92% humidity for 15 minutes. After annealing, extrude the slurry through a casting die to form a continuous film approximately 1.5mm thick, which is then directly deposited onto a cooling steel belt with a surface temperature of 5℃. From the moment the slurry contacts the cooling steel belt, the center temperature of the film drops below 30℃ within approximately 30 seconds. Scrape off the film, dry it at 50℃ until the moisture content reaches 12.0%, then pulverize and sieve. Test results show that the resistant starch content is 7.8%, the GI value is 63, and the RS3 melting temperature is 121℃. Example 5 (corn starch slurry annealing, extrusion molding + cold air quenching) Take 1000g of corn starch, add 1000mL of water, and stir to make a uniform slurry with a moisture content of about 50%. Anneal at 62℃ and 90% humidity for 14 minutes. After annealing, extrude the slurry through a slit die into a strip material with a thickness of about 1.5mm. Immediately after extrusion, it enters a 0℃ cold air tunnel (wind speed 3m / s). The temperature of the strip material drops below 28℃ at the exit of the cold air tunnel, and the entire process takes about 70 seconds. Dry at 48℃ until the moisture content is 12.5%, then pulverize and sieve. Test results show that the resistant starch content is 7.3%, the GI value is 64, and the RS3 melting temperature is 120℃. Comparative Example 1 (moisture content below 40%, the paste-like material cannot be spread evenly) Reducing the water content in Example 1 to 600 mL (approximately 38% water content) resulted in a paste-like rather than a flowable slurry, which could not be evenly spread on a scraper film dryer. Annealing and subsequent treatments were performed under the conditions of Example 1. The product had a resistant starch content of only 5.8% and a GI value of 68. This demonstrates that when the water content is below 40%, the material does not possess slurry-like properties and is not suitable for the method described in this patent. Comparative Example 2 (moisture content exceeds 60%, annealing efficiency decreases) The water content in Example 1 was increased to 2500 mL (approximately 71% water content). During annealing, the degree of gelatinization was too high (reaching 72%), and the microcrystal retention rate was less than 50%. The product had a resistant starch content of only 5.2% and a GI value of 70. This demonstrates that when the water content exceeds 60%, the starch concentration is too low, and the efficiency of ordered rearrangement decreases significantly. Comparative Example 3 (Spreading without simultaneous rapid cooling) The spreading and rapid cooling of Example 1 were performed in separate steps: the annealed slurry was first spread and dried into thin sheets on a heated drum, and then removed and allowed to cool naturally to below 35°C at room temperature (approximately 15 minutes). The product had a resistant starch content of 5.5%, a GI value of 68, and an RS3 melting temperature of 110°C. This demonstrates that rapid cooling must be performed simultaneously after spreading; otherwise, severe retrogradation of RS3 will occur. Comparative Example 4 (Slurry Annealing of Gluten Protein Raw Material) The raw material in Example 1 was changed to high-gluten wheat flour (14% protein, 33% wet gluten), and water was added to make a slurry with a moisture content of 55%. The annealing temperature was 51°C. During the annealing process, the gluten proteins in the slurry were fully hydrated to form a strong network. After annealing, it became a viscoelastic dough that could not be spread. Even if forced to spread, the wet gluten retention rate of the product was only 55%, and it had lost its high-gluten processing properties. This proves that the slurry route is not suitable for raw materials containing gluten proteins. Comparative Example 5 (intermediate zone with 36% moisture content, extrusion molding still failed) Take 1000g of rice flour, add 560mL of water, and stir to make a paste with a moisture content of approximately 36%. Anneal at 65℃ and 92% humidity for 20 minutes (5 minutes longer than in Example 1 to attempt to compensate for insufficient moisture). After annealing, feed the paste into a twin-screw extruder and extrude it into a strip through a slit die. After extrusion, it is rapidly cooled in a 0℃ cold air tunnel. During extrusion, the material flow is uneven, and irregular cracks and thickness fluctuations appear on the surface of the strip. The product has a resistant starch content of only 5.3%, a GI value of 69, and a coefficient of variation of 18% for samples taken from different parts (compared to only 3% in Example 1). This proves that when the moisture content is below 40%, it is impossible to achieve the product standard regardless of whether scraper spreading or extrusion molding is used. Comparative Example 6 (Boundary verification at 35% moisture content, extrusion molding failed) Take 1000g of rice flour, add 540mL of water, and stir to prepare a material with a moisture content of approximately 35%. Treat it under the same conditions as Comparative Example 5. The product has a resistant starch content of only 4.8% and a GI value of 71. Combined with Comparative Example 1 (38%) and Comparative Example 5 (36%), it is fully demonstrated that the entire moisture content range of 35%-39% is not suitable for the slurry annealing route. Comparative Example 7 (annealing temperature below the lower limit of the window) The annealing temperature in Example 1 was changed to 48°C, and the annealing time was extended to 20 minutes. The product had a resistant starch content of 5.1% and a GI value of 68. This demonstrates that the starch molecular chain mobility is insufficient when the annealing temperature is below 50°C. Comparative Example 8 (annealing temperature higher than the upper limit of the window) The annealing temperature in Example 1 was changed to 68°C, and the annealing time was shortened to 8 minutes. The degree of gelatinization reached 75%, the microcrystal retention rate was only 25%, the resistant starch content of the product was 4.9%, and the GI value was 70. This demonstrates that when the annealing temperature is higher than 65°C, a large amount of residual microcrystals melt and collapse. Comparative Example 9 (protein content close to the upper limit) Defatted soybean flour and corn starch were blended in a specific ratio to produce 1000g of a mixed powder with a protein content of approximately 9.5%. The mixture was then annealed in a slurry state according to the conditions of Example 1. During annealing, protein flocculation particles appeared on the surface of the slurry, resulting in decreased spreading uniformity. The product had a resistant starch content of 7.1% (barely meeting the standard), but fine yellowish-brown particles (Maillard reaction products) were visible after passing through an 80-mesh sieve. The product's appearance and uniformity did not meet commercial requirements. This demonstrates that product appearance and uniformity are substandard when the protein content exceeds 10%. Detection methods Resistant starch content: AOAC 2002.02 standard method was used. GI value: based on the ISO 26642:2010 standard method. RS3 melting temperature: Differential scanning calorimetry (DSC) was used, with a heating rate of 10℃ / min, nitrogen atmosphere, and a temperature range of 10-180℃. Particle morphology: The particle morphology of the product was observed using a scanning electron microscope (SEM); the aspect ratio of the particles was measured using a laser particle size analyzer. Material film temperature: measured in real time using an infrared thermometer. Moisture content: determined by the first method (direct drying method) of GB 5009.3-2016. Industrial applications The core equipment of this invention can be flexibly selected according to different spreading methods: scraper film dryers, casting machines, extrusion molding machines, etc., all of which are mature equipment widely used in the chemical and food industries. The entire production line includes a slurry tank, a constant temperature and humidity annealing tank, an integrated spreading and rapid cooling molding equipment, a low temperature drying oven, and a crushing and screening equipment. While the energy consumption for drying via the slurry route is higher than that of the powder conditioning route, its advantage lies in the fact that it does not require high-pressure atomization conditioning equipment and fluidized bed quenching systems, resulting in lower equipment investment. For starch processing companies that already have drum drying equipment or cast casting equipment, they only need to add a constant temperature and humidity annealing tank to enter the low-GI market, with extremely low equipment modification costs. This method, together with the core powder conditioning and annealing patent, constitutes a complete protection network for the "material pretreatment form" - powder conditioning (moisture content 20%-35%) falls within the scope of the core patent, slurry annealing (moisture content 40%-60%) falls within the scope of this patent, and materials in the intermediate zone with a moisture content of 35%-40% cannot achieve product compliance regardless of the molding method used.

Claims

1. A low glycemic index cereal powder or starch, characterized in that, The cereal flour or starch is prepared by a method comprising the following steps: a. Pulping: Mix low-protein or gluten-free starchy raw materials with water and stir to make a uniform, flowable slurry with a water content of 40%-60%; b. Slurry annealing: The slurry material is kept in a constant humidity environment with a relative humidity of 90%-95% for 10-20 minutes within a temperature window of 50-65℃, so that the partially gelatinized amylose molecules rearrange orderly along the surface of the residual natural starch microcrystals to generate RS3 type resistant starch. c. Spreading and rapid cooling integrated molding: The annealed slurry material is spread into a thin layer with a thickness of no more than 3 mm within 90 seconds and simultaneously cooled to below 35°C. The spreading action itself is a rapid cooling method, which enables the RS3 lattice to be quickly shaped during the spreading process. d. Low-temperature drying: The cooled and shaped thin-layer material is dried at a temperature not exceeding 60°C until the moisture content is below 13%, then crushed and sieved to obtain the product; The grain powder or starch simultaneously meets the following requirements: resistant starch content ≥7% (determined according to AOAC 2002.02 standard method), RS3 type resistant starch melting temperature ≥120℃ (determined by differential scanning calorimetry), GI value ≤65, and the ingredient list contains only the raw material itself.

2. The low glycemic index cereal powder or starch according to claim 1, characterized in that, The low-protein or gluten-free starch-containing raw material mentioned in step a is selected from any one or more of rice flour, corn starch, potato starch, sweet potato starch, tapioca starch, buckwheat flour, millet flour, sorghum flour, oat starch, pea starch, and mung bean starch; the protein content of the raw material is ≤10%, and it does not contain gluten protein.

3. The low glycemic index cereal powder or starch according to claim 1, characterized in that, The integrated spreading and rapid cooling molding described in step c is achieved using a scraper-type film dryer. This equipment includes a heating drum and a cooling drum, which are arranged side by side. After the scraper peels the film off the heating drum, it is directly introduced onto the surface of the cooling drum, with a transfer time of no more than 5 seconds. The slurry material is first spread on the surface of the heating drum to form a film with a thickness of 1-2 mm. After preliminary dehydration to a moisture content of 30%-35%, it is transferred to the cooling drum for rapid cooling to below 35°C within 90 seconds. The surface temperature of the heating drum is 75-85°C. Under the condition that the moisture content of the material is ≥45%, the water evaporation absorbs heat, so that the actual temperature of the material film does not exceed 68°C, and no RS3 thermal damage is caused.

4. The low glycemic index cereal powder or starch according to claim 1, characterized in that, The integrated spreading and rapid cooling molding described in step c is achieved by casting molding. The annealed slurry is extruded through a casting die to form a continuous film with a thickness of 1-2 mm. The film falls directly onto a cooling steel strip at 0-10℃, and rapid cooling and shaping are completed at the same time as spreading and forming the film.

5. The low glycemic index cereal powder or starch according to claim 1, characterized in that, The integrated spreading and rapid cooling molding described in step c is achieved by extrusion molding. The annealed slurry is extruded through a slit die into a strip material with a thickness of 1-2 mm. After extrusion, it immediately enters a cold air tunnel at 0-5℃, and rapid cooling is completed at the same time as molding.

6. The low glycemic index cereal powder or starch according to claim 3, characterized in that, The surface temperature of the cooling drum of the scraper-type film dryer is 0-10℃; the starting point of the 90-second timing is the moment when the slurry comes into contact with the heating drum, and the ending point of the timing is the moment when the film leaves the cooling drum.

7. The low glycemic index cereal powder or starch according to claim 1, characterized in that, The slurry annealing temperature in step b is 60-65℃, the annealing time is 12-15 minutes, and the raw material is rice flour or corn starch.

8. The low glycemic index cereal powder or starch according to claim 1, characterized in that, The water content of the slurry material in step a is 45%-55%, and the thickness of the thin layer in step c is 1-2 mm.

9. The low glycemic index cereal powder or starch according to claim 1, characterized in that, The low-temperature drying temperature described in step d is 45-55℃.

10. The use of the low glycemic index cereal powder or starch according to any one of claims 1-9 in the preparation of low GI foods, pharmaceutical excipients, pet food, aquatic feed or biodegradable packaging materials.